Energy efficiency standards and labels for electric rice cookers in Malaysia / Noor Dina Ghazali - Noor Dina , Ghazali (2013)
Energy efficiency standards and labels for appliances, equipment and lighting are being implemented in many countries around the world where they have a potential for very large energy savings, very cost effective and environmental friendly. Malaysia is one of the countries that being implicates this program to save energy consumption for the future. In this study, standards and labelling program is being implemented to electric rice cooker on the Malaysian household. The surveys have been conducted to 350 respondents evaluate the energy consumption when electric rice cooker is being used every day. Energy efficiency standards of electric rice cookers is defined as annual energy consumption. After the standard is in place, three types of energy labels are established. One type of the labels was selected according to the respondents input. The study also examines the possible changes in annual energy consumption of Malaysian households in the future by predicting the energy, economical and environmental impacts due to the standards and labels implementation for electric rice cooker. Once appliance standards and labelling programs have been implemented, it is necessary to evaluate their effectiveness. The energy will save about 11,240 GWh, the bill savings will be about RM 3,770 million. The total emissions reduction are about 5,643,967 ton of carbon dioxide, 34,527,204 kg of sulphur dioxide, 16,149,072 kg of nitrogen oxide and 3,371,253 kg of carbon monoxide.